Impact of the Coronavirus Disease 2019 (COVID-19) Pandemic on Imaging Case Volumes - Naidich, Jason J. (J Am Coll Radiol, 2020)
OBJECTIVE: The coronavirus disease 2019 (COVID-19) pandemic has had significant economic impact on radiology with markedly decreased imaging case volumes. The purpose of this study was to quantify the imaging volumes during the COVID-19 pandemic across patient service locations and imaging modality types. METHODS: Imaging case volumes in a large health care system were retrospectively studied, analyzing weekly imaging volumes by patient service locations (emergency department, inpatient, outpatient) and modality types (x-ray, mammography, CT, MRI, ultrasound, interventional radiology, nuclear medicine) in years 2020 and 2019. The data set was split to compare pre-COVID-19 (weeks 1-9) and post-COVID-19 (weeks 10-16) periods. Independent-samples t tests compared the mean weekly volumes in 2020 and 2019. RESULTS: Total imaging volume in 2020 (weeks 1-16) declined by 12.29% (from 522,645 to 458,438) compared with 2019. Post-COVID-19 (weeks 10-16) revealed a greater decrease (28.10%) in imaging volumes across all patient service locations (range 13.60%-56.59%) and modality types (range 14.22%-58.42%). Total mean weekly volume in 2020 post-COVID-19 (24,383 [95% confidence interval 19,478-29,288]) was statistically reduced (P = .003) compared with 33,913 [95% confidence interval 33,429-34,396] in 2019 across all patient service locations and modality types. The greatest decline in 2020 was seen at week 16 specifically for outpatient imaging (88%) affecting all modality types: mammography (94%), nuclear medicine (85%), MRI (74%), ultrasound (64%), interventional (56%), CT (46%), and x-ray (22%). DISCUSSION: Because the duration of the COVID-19 pandemic remains uncertain, these results may assist in guiding short- and long-term practice decisions based on the magnitude of imaging volume decline across different patient service locations and specific imaging modality types.